The Changing World of Mobile Communications 5G, 6G and the Future of Digital Services - Ahokangas, Petri; Aagaard, Annabeth (Springer Nature, 2024)
This open access book from the world's first 6G Flagship research program at the University of Oulu, Finland, provides a multi-disciplinary and insightful overview of the subject, with contributions from experts in the field. Today's fourth generation of mobile connectivity services (4G) are available everywhere, and adoption of fifth generation (5G) networks is well underway. Compared to 4G, 5G has already brought about new business opportunities and enabled seamless virtual and augmented reality services, but also raised serious concerns on data privacy and security and the use of artificial intelligence. The sixth generation (6G) networks are already in R&D phase aiming at deployment in 2030. We need to understand today what 5G evolution and 6G may bring for the future of service delivery and how they will influence us. The contributions answer what 5G, its evolution, and 6G will be about; what kind of impacts 5G and 6G will have on future digital services, businesses, and society; how we could benefit from 5G and 6G innovations; and how 5G and 6G should be regulated in the future. Future 5G evolution and 6G are not only about moving toward faster, better, and more secure networks providing the basis for innovative digital services, they are also going to bring about a huge digital disruption that will affect all levels of society. This book will be of great interest to academics and students of management, telecommunications and digital innovation, as well practitioners and policymakers looking to the future of business.